Does land tenure insecurity discourage tree planting?: evolution of customary land tenure and agroforestry management in Sumatra - Otsuka, Keijiro; Suyanto, S.; Tomich, Thomas P. (International Food Policy Research Institute, 1997)
It is widely believed that land tenure insecurity under a customary tenure system leads to socially inefficient resource allocation. This article demonstrates that land tenure insecurity promotes tree planting, which is inefficient from the private point of view but could be relatively efficient from the viewpoint of the global environment. Regression analysis, based on primary data collected in Sumatra, indicates that tenure insecurity in fact leads to early tree planting. It is also found that customary land tenure institutions have been evolving towards greater tenure security responding to increasing scarcity of land.